FIGURATIVE LANGUAGE IN BILLIE EILISH'S SECOND STUDIO ALBUM "HAPPIER THAN EVER" - Pattisahusiwa, Syasa Diarani Yah'ma (Journal of English Literature and Linguistic Studies, 2025)
The purpose of this study is to figure out the varieties of figurative language and imagery used in BillieEilish's second studio album “Happier Than Ever." The researcher analyzes the data using Perrine's(1991) figurative language theory and Robert DiYanni's (2004) imagery theory. The qualitative researchmethod was employed by the researcher. The researcher used purposive sampling in order to gather allthe data. This research used a semantic approach to determine the connection between phrases,sentences, and words. The results revealed that there are five forms of figurative language featured inBillie Eillish second studio album "Happier Than Ever," which are synecdoche, metaphor, symbol,hyperbole, and simile. The study discovered approximately 16 figurative language extracts. In addition,the researcher discovered four imageries Billie Eilish's sophomore studio album "Happier Than Ever":visual imagery, auditory imagery, kinesthetic imagery, and organic imagery. The researcher discovered52 imagery extracts.